Idiopathic Dilated Cardiomyopathy: Clinical Profile of 100 Patients - Banerjee, Sajal K; Rahman, Fazlur; Salman, Mohammad; Siddique, Md Abu; Zaman, SM Mustafa; Anam, Khairul; Rahman, Mukhlesur; Ahmed, Md Khurshed; Rasheed, MA; Akhter, Nargis; Faruque, M; Jamiluddin, Mir; et al. (University Heart Journal, 2011)
Clinicians continue to face the challenges of identifying and treating the idiopathic dilated cardiomyopathy to improve symptoms and survival. A study on idiopathic dilated cardiomyopathy was done in the Department of Cardiology, University Cardiac Center, Bangabandhu Sheikh Mujib Medical University, Dhaka, from January 2004 to December 2009. The aim of this study was to examine clinical profile of patients with idiopathic dilated cardiomyopathy. The age range was 18 to 65 years and 70% subjects were male. Most common symptom was dyspnea (86%) and cough (75%). 75% subjects had sinus tachycardia, 42% had ventricular ectopics and 40% had left bundle branch block. Mean diastolic dimension was 60±9 mm, ejection fraction was 28±8%, left atrial dimension was 40±6 mm and 36% were having mitral regurgitation. Left ventricular failure (75%) and various type of arrhythmias (62%) were the main complications. 8% subjects were died during hospital stay. Hence the clinical presentation of idiopathic dilated cardiomyopathy varies from patient to patient, but most patients present later, i.e. at some point in the spectrum of heart failure. Key words: Idiopathic dilated cardiomyopathy; left ventricular failure; ventricular ectopics. DOI: 10.3329/uhj.v6i1.7182 University Heart Journal Vol.6(1) 2010 pp.9-12